2021
DOI: 10.3389/fpsyt.2020.606041
|View full text |Cite
|
Sign up to set email alerts
|

Co-developing a Mental Health and Wellbeing Chatbot With and for Young People

Abstract: There are many young people who experience mental health and wellbeing challenges. A potential negative mental health trigger for some youth is a struggle to cope with stress at school, feelings of depression and anxiety and availability of adequate help for these stressors. In response to youth needs a mental health and wellbeing Chatbot has been co-developed with youth, technology partners and expert stakeholders. An element of the Chatbot is powered by artificial intelligence and rules based AI using natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 65 publications
1
45
0
3
Order By: Relevance
“…In a recent scoping review on mental health chatbots, 3 studies that Abd-Alrazaq et al looked at found that users would like to personalise their own chatbot by choosing the gender and appearance (Abd-Alrazaq et al, 2021 ). Another recent paper reported that young people wanted a chatbot with a gender neutral name that was inspiring, charismatic, fun, friendly and had an empathic and humorous personality (Grové, 2021 ). In our study, desirable features included a human persona who was female or gender neutral, aged approximately mid-thirties with an extroverted and supportive personality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent scoping review on mental health chatbots, 3 studies that Abd-Alrazaq et al looked at found that users would like to personalise their own chatbot by choosing the gender and appearance (Abd-Alrazaq et al, 2021 ). Another recent paper reported that young people wanted a chatbot with a gender neutral name that was inspiring, charismatic, fun, friendly and had an empathic and humorous personality (Grové, 2021 ). In our study, desirable features included a human persona who was female or gender neutral, aged approximately mid-thirties with an extroverted and supportive personality.…”
Section: Discussionmentioning
confidence: 99%
“…While many popular mental health chatbots exist, few studies have reported on how user groups can contribute to co-design as it is important to consider the user needs when designing content and features for this application. A few recent studies have involved young people in the design process to co-develop mental health and wellbeing chatbots targeted at under 18 s (Audrey et al, 2021 ; Grové, 2021 ). Another study by Easton et al reported on co-designing content for a health chatbot by involving patients with lived experiences (Easton et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The application of two filters resulted as follows: first, 22 articles were published in 2020; second, and after selecting health topic as a domain area, 11 articles emerged as a final result. In the end, this material was spread across these different Frontier Journals categories: digital health ( N = 7) ( 20 26 ); public health ( N = 2) ( 27 , 28 ); and psychiatry ( N = 2) ( 29 , 30 ). All 11 titles were analyzed through a double review discussion.…”
Section: Resultsmentioning
confidence: 99%
“…Gençlerle Birlikte ve Gençler İçin Akıl Sağlığı ve Refahı Sohbet Robotu Geliştirmek isimli makalede ise Chatbot'un nasıl geliştirildiği tartışılmaktadır ve bu dijital araçtan yararlanacak kilit paydaşlar olan gençlerle katılımcı, ortak tasarım sürecini vurgulamaktadır. Görüşmelerden ve anketlerden elde edilen araştırmalar, Chabot kişiliğinin yaratılması ve karakter tasarımı hakkında bilgi verilmektedir [13]. Sağlık Sohbet Robotu isimli çalışmada hastaların sohbet robotu ile etkileşime girmesine yardımcı olmaktadır.…”
Section: Introductionunclassified